Prominin2 Drives Ferroptosis Resistance by Stimulating Iron Export - Brown, Caitlin W.; Amante, John J.; Chhoy, Peter; Elaimy, Ameer L.; Liu, Haibo; Zhu, Lihua Julie; Baer, Christina E.; Dixon, Scott J.; Mercurio, Arthur M. (Developmental cell, 2019)
Ferroptosis, regulated cell death characterized by the iron-dependent accumulation of lethal lipid reactive oxygen species, contributes to tissue homeostasis and numerous pathologies, and it may be exploited for therapy. Cells differ in their sensitivity to ferroptosis, however, and a key challenge is to understand mechanisms that contribute to resistance. Using RNA-seq to identify genes that contribute to ferroptosis resistance, we discovered that pro-ferroptotic stimuli, including inhibition of the lipid hydroperoxidase GPX4 and detachment from the extracellular matrix, induce expression of prominin2, a pentaspanin protein implicated in regulation of lipid dynamics. Prominin2 facilitates ferroptosis resistance in mammary epithelial and breast carcinoma cells. Mechanistically, prominin2 promotes the formation of ferritin-containing multivesicular bodies (MVBs) and exosomes that transport iron out of the cell, inhibiting ferroptosis. These findings reveal that ferroptosis resistance can be driven by a prominin2-MVB-exosome-ferritin pathway and have broad implications for iron homeostasis, intracellular trafficking, and cancer. [Display omitted] •Pro-ferroptotic stimuli induce expression of the pentaspanin protein Prominin2•Prominin2 facilitates ferroptosis resistance in epithelial and carcinoma cells•Prominin2 promotes formation of ferritin-containing multivesicular bodies and exosomes•Exosomal transport of ferritin out of the cell inhibits ferroptosis Cells differ in their capacity to resist ferroptosis but mechanisms that contribute to resistance are not well understood. Brown et al. demonstrate that resistant cells are characterized by their ability to induce expression of Prominin2, which stimulates the formation of ferritin-containing multivesicular bodies/exosomes that transport iron out of the cell.